Antidiabetic and antiulcerative potential of Garcinia lanceifolia Roxb. bark - Nilutpal Sharma Bora; Partha Sarathi Bairy; Abdus Salam; Bibhuti Bhusan Kakoti (SpringerOpen, 2020)
Abstract Background Garcinia lanceifolia Roxb. has been used by many ethnic communities of Northeast India to mitigate various disorders like dyspepsia, ulcers, diabetes, etc. However, a robust scientific study on its antidiabetic and antiulcer potential is unavailable till date. The aim of this present study is to scientifically validate if the antidiabetic and antiulcer effects reported by the ethnic tribes of Assam has any scientific value or not. The effects were tested in adult Wistar albino rats using approved animal models for preclinical testing of pharmacological activities. Results The hydroalcoholic extract of the bark of Garcinia lanceifolia Roxb. was prepared and its LD50 was calculated. The LD50 was determined to be greater than 5000 mg/kg body weight. The extract at doses of 250 mg/kg body weight and 500 mg/kg body weight was found to exhibit a very potent dose-dependent antidiabetic activity. The results were backed by a battery of test including analysis of serum levels of blood glucose, lipid profiles, in vivo antioxidant enzymes, and histopathological studies. Evidence of dose-dependent antiulcer activity of the extract was backed by robust scientific data. It was found that HAEGL induced a significant dose-dependent increase in the ulcer index in both alcohol-induced and acetic acid-induced ulcer models, which was evident from the macroscopic observation of the inner lining of the gastric mucosa and the histological evaluation of the extracted stomach. Conclusion The results suggested that the bark of Garcinia lanceifolia (Roxb.) has significant antidiabetic and antiulcer potential. Further studies with respect to the development herbal dosage forms and its safety evaluation are required.